Обращения как способ выражения эмоций (на материале русского, белорусского и словацкого языков) - Калечиц, Елена (Studia Rossica Posnaniensia, 2019)
Emotions put their imprint on all language levels and, most likely, are manifested in almost all appeals. The paper analyzes the appeals, synonymous with the word “grandmother”, which perform pragmatic and expressive functions. On this basis, we call them emotives and emotives-regulators. Some nuances of their use in Russian, Belarusian and Slovak are described. The positive national and international emotional meaning of the appeals under consideration is underlined.